Delving the underlying factors of homeless women who work as prostitutes in Kuala Lumpur City Centre / Nor Amalina Mohd Adib - Mohd Adib, Nor Amalina (2018)
This thesis delve the underlying factors of homeless women who work as prostitute in Kuala Lumpur City Centre. This study adopted a qualitative approach through in-depth interview and observation among ten (10) homeless women who work as prostitutes. The respondents ages ranged from 31 to 60 years old. Out of ten respondents, six of them are Malays, two Indian (one respondents were converted to Islam), one Chinese (converted to Islam) and one Bumiputera Sarawakian. All ten respondents are among Malaysian nationality.